GIS application in monitoring development plan implementation in Malaysia: Weaknesses and potential - Abdullah, Muhammad Faris; Abdullah, Alias; Zahari, Rustam Khairi (2009)
Monitoring of development plans implementation is gaining more attention than before by the planning authorities in Malaysia. Pilot plan monitoring projects are being conducted in order to develop the most suitable monitoring mechanism. Since GIS use is widespread in development plan preparation process in Malaysia, there have also been efforts to bring GIS into the monitoring stage of the plan. This paper looks at the present practices of states planning authority in Malaysia in monitoring the implementation of their State Structure Plans (SSP). Interview surveys were conducted with all states planning authority that already have their SSP gazetted. It was found that, although many have not had proper monitoring practices in place, some had already been using GIS for the purpose of monitoring the implementation of their plans. This paper discusses the weaknesses of the monitoring systems being used by planning authorities presently and provides an alternative monitoring model which can overcome the weaknesses of the present systems. The discussion provided in this paper could be helpful to planning authorities who wish to develop their plan monitoring system in the future.